2018
DOI: 10.1371/journal.pone.0198005
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological surveillance of HIV-1 transmitted drug resistance among newly diagnosed individuals in Shijiazhuang, northern China, 2014–2015

Abstract: BackgroundThe widespread use of antiretroviral therapy (ART) has led to considerable concerns about the prevalence of transmitted drug resistance (TDR). Sexual contact, particularly men who have sex with men (MSM) was the most prevalent form of HIV transmission in Shijiazhuang. Hence, we conducted an epidemiological surveillance study on TDR among newly diagnosed individuals who infected-HIV through sexual contact in from 2014–2015.MethodsGenotypic resistance mutations were defined using the WHO-2009 surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 41 publications
5
6
1
Order By: Relevance
“…As the increase in TDR will affect the antiviral treatment and the spread of drug resistance, the surveillance of TDR should be strengthened, and measures to curb the increase of TDR should be adopted. A significant difference was observed between the prevalence of TDR and marital status and subtype, which contradicted from the results of a previous study [ 17 , 28 ]. When marital status was used as a categorisation parameter, unmarried individuals were most likely to develop drug resistance.…”
Section: Discussioncontrasting
confidence: 94%
“…As the increase in TDR will affect the antiviral treatment and the spread of drug resistance, the surveillance of TDR should be strengthened, and measures to curb the increase of TDR should be adopted. A significant difference was observed between the prevalence of TDR and marital status and subtype, which contradicted from the results of a previous study [ 17 , 28 ]. When marital status was used as a categorisation parameter, unmarried individuals were most likely to develop drug resistance.…”
Section: Discussioncontrasting
confidence: 94%
“…However, drug resistance and clustering in the transmission network were independent of each other, which is consistent with the results of a study in Shijiazhuang [ 71 ]. The clusters containing drug-resistant individuals in the genetic transmission network accounted for 13.5% of the study population, and the proportion increased over time, which may be caused by an increase in the number of drug-resistant individuals over time.…”
Section: Discussionsupporting
confidence: 90%
“…The RT K103N mutation found in two strains can reduce EFV and NVP susceptibility by about 20-and 50-fold, respectively 44 . Drug resistance analysis demonstrated that 2.4% of HIV-1 isolates contained at least one NNRTI (K101E, K103N) or PI (M46I) SDRMs, the overall prevalence of TDR was lower than previous reports in Zhejiang (11.1%) and Shijiazhuang (6.1%) among treatment-naïve HIV-infected individuals 45,46 , but similar to a nationwide cross-sectional survey about prevalence of TDR (3.6%) in 2015 in China 47 . Although the rate of TDR remained relatively low in Chinese blood donors in this study, the detection of 3 major NNRTI mutations and 1 PI mutation underlined the importance of a continuous surveillance of resistance mutations.…”
Section: Discussionsupporting
confidence: 69%